Azebaycan’ın İlk Savaş Pilotu Ferruh Ağa Gayıbov The First Combat Pilot of Azerbaijan- Farrukh Gayıbov- - KEMALOĞLU, MUHAMMET (Journal of History Culture and Art Research, 2014)
Ferruh Ağa Gayıbov Azerbaycanlı ilk şavaş pilotudur. İlya Muromets no–16 adlı bombardıman uçağının personelidir. I.Dünya Savaşına katılmıştır. Çar ordusunda Topçuların Tanrısı diye kabul edilen Aliağa Şıhlinski’nin de akrabasıdır. Ferruh Ağa 2 Ekim 1891’de, Kazak ilinin Sınır Salahlı köyünde doğmuştur. Tiflis Askeri Okulunda okur. Üsteğmen rütbesinde iken 12 Eylül 1916’da Batı cephesi karargâhının emri ile Borına’ya saldırır, Almanların mevzilerini ve mevkilerini bombalar. Onun uçağına doğru 4 alman savaş uçağı saldırıya geçer. Gayıbov onların üçünü imha eder ancak uçağının aldığı darebeden dolayı yere çırparak hayatını kaybeder. ŞÉ™mistan NÉ™zirli’den yaptığmız AzÉ™rbaycanın İlk HÉ™rbi TÉ™yyarÉ™çisi Ferruh Ağa Gayıbov adlı bu çeviri eser Ferruh Ağa Gayıbov’u tarihin derin sayfalarından çıkarmıştır. Abstract Ferruh Gayıbov was the first Azerbaijani combat pilot. He was the bombardier in Ilya Muromets no–16 bomber aircraft. He joined World War I. He was a relative Aliaga Şıhlinski whose name called "the God of Artillery," in the Tsarist army. Ferruh Agha was born in 2 October 1891, in the village of Salahlı Kazakh. He studied at Tbilisi Military School. When he was a first lieutenant, he attacked to the Boriana with the order of West Front Headquarter and bombed German positions and locations in September 12, 1916. Four German bomber aircraft attacked his plane. Gayıbov destroyed three of them but his plane got shot and he lost his life. Our translation of AzÉ™rbaycanın İlk HÉ™rbi TÉ™yyarÉ™çisi Ferruh Ağa Gayıbov by Şemistan Nezirli, has revealed Ferruh Agha Gayıbov from the depths of history.